Simulation of proton exchange membrane electrolyzer: Influence of bubble covering. (29th May 2022) - Su, Xin; Xu, Lijun; Hu, Bing
Abstract: The bubble covering phenomenon has been considered one of the most critical factors affecting Proton Exchange Membrane Electrolysis Cell (PEMEC) at high current densities. However, the relationship between bubble dynamics and electrochemistry has not been clearly defined. This study analyzes the bubble coverage and PEMEC performance under different input conditions and develops a mathematical model of PEMEC incorporating bubble dynamics. The model successfully predicted the polarization curves and coincided with the experimental data. The results show that bubble coverage increases with increasing current density, bubble detachment radius, and temperature. It decreases with increasing pressure and water inlet velocity. Bubble coverage is influenced by temperature, pressure, wettability, current density, and water inlet velocity. Meanwhile, bubbles covering the electrode deteriorate the performance of the PEMEC, leading to higher overpotentials and lower efficiencies, which becomes more apparent with increasing current density. This paper elucidates the relationship between bubble growth/detachment, bubble coverage, and electrochemistry for the first time, and the results can provide a reference for the development and optimization of high-performance PEMEC. Highlights: A bubble dynamic model of a PEMEC was developed and verified by experiments. Considering Bubble dynamics, bubble coverage and overpotential effects in this model. Assessing the effects of temperature, pressure and water velocity on bubble coverage. Bubble coverage results in higher overpotential and lower efficiency.